Antecedents of Corporate Entrepreneurship in SMEs: Evidence from an Emerging Economy. (1st September 2016) - Hughes, Mathew; Mustafa, Michael
Abstract : Corporate entrepreneurship (CE) research has reached a certain degree of consensus around five core internal antecedents that enable CE, but consensus remains focused on large‐sized firms in Western economies. Using institutional theory, we argue that contextual factors may undermine the viability of internal antecedents in emerging economy contexts. Our qualitative study shows that the organization of the internal environments for CE among service sector Kenyan SMEs is much more interactive and complex than currently presented in the literature. Specifically cultural and contextual factors appear to influence the extent to which the antecedents are able to produce CE activity. Our findings provide a more fine‐grained depiction of the internal environment for CE in emerging economy SMEs.